2018
DOI: 10.3389/fpsyg.2018.02135
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana Use and Depressive Symptoms; Gender Differences in African American Adolescents

Abstract: Introduction: This study aimed to examine gender differences in the bidirectional associations between marijuana use and depressive symptoms among African American adolescents. The study also tested gender differences in the effects of socioeconomic status, maternal support, and friends’ drug use on adolescents’ depressive symptoms and marijuana use.Methods: This is a secondary analysis of the Flint Adolescent Study (FAS). Six hundred and eighty one African American adolescents (335 males and 346 females) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 141 publications
(156 reference statements)
1
12
0
Order By: Relevance
“…Participants were asked about the frequency of their marijuana use over the past 30 days at all waves (52). This measure was used between 2000 and 2012.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked about the frequency of their marijuana use over the past 30 days at all waves (52). This measure was used between 2000 and 2012.…”
Section: Methodsmentioning
confidence: 99%
“…[17][18][19] Some evidence suggests that MDRs also apply to tobacco use, meaning that high SES Blacks and Hispanics are more likely to use tobacco and alcohol, compared to high SES Whites. [23][24][25][26] We are, however, not aware of any previous studies on MDRs on second-hand smoke exposure. We conducted this study to test whether race and ethnicity interact with educational attainment on workplace second-hand smoke exposure in American adults who were employed.…”
Section: Introductionmentioning
confidence: 95%
“…In longitudinal studies, gender differences in the relationship between adolescent cannabis use and anxiety/depressive symptoms have shown an opposite trend to those reported by cross-sectional studies discussed above. In a large adolescent sample balanced for gender, baseline cannabis use at age 16 predicted increases in depressive symptoms in over three years among male, but not, female African American adolescents (Assari et al, 2018 ). Another study found an association between escalating cannabis use and decreased connectivity between nucleus accumbens and medial PFC that predicted higher levels of depressive symptoms (Lichenstein et al, 2017 ).…”
Section: Cannabismentioning
confidence: 99%